If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 * 0 + -9y = -81 Multiply 9 * 0 0 + -9y = -81 Anything times zero is zero. 0 + -9y = -81 Remove the zero: -9y = -81 Solving -9y = -81 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '-9'. y = 9 Simplifying y = 9
| 3/12n=15/6 | | 9x*9y=-8 | | 9x-9y=-81 | | 12x+6=349-28 | | y=-1/7x+12/7 | | 4(3t+-2)+3-89=89 | | 4(3+-2)+3-89=89 | | -4*0-8y=32 | | -6(0)-8y=48 | | 3p+5q-6(3p-3q+3r)= | | -4-8y=32 | | 0.35t^2-50t+1000=0 | | 0.05*t^2+54*t-500=0 | | 4(0)+10y=40 | | 4(0)+10y=42 | | 6p+5q-7(6p-3q+7r)= | | 7/8(p)=-16/4 | | x*2+8x-9=0 | | 4u+2v-2(4u-7v+3w)= | | x^2+4x^2-32x=0 | | 8/9-5m/9=14/9 | | x-6/7=23 | | 12=13/4x-10 | | 1/2-2/3x=5 | | 4-5(y+3)+6y=7 | | 2(3x-4)=3(2x+1)-11 | | 1/1/k | | 16v-81v^3= | | y=-3/2*2-3 | | y=-3/2*3-3 | | 49y^2+42y+9= | | y=-7/10(-7)+7 |